Hubungan Motivasi Kerja Dengan Perilaku Penggunaan Alat Pelindung Diri Pada Petugas Sampah Medis Di RSU Bangli - Putu Dewi Nara Santi; I Nyoman Gede Suyasa; I Wayan Jana (Jurnal Kesehatan Lingkungan (JKL), 2019)
Hospital health facilities, is a workplace that is heavily loaded with potential health and safety hazards of its workers. The risk of health problems and accidents becomes greater because health facilities are labor-intensive workplaces. The purpose of this study to determine the relationship of work motivation with the behavior of the use of personal protective equipment (PPE) to medical waste officers at Bangli General Hospital. The type of this research is observational research with cross sectional approach implemented in Bangli General Hospital, with 36 respondents. Data were collected by using questionnaire and univariate and bivariate analysis. Result of this research, there are 25% resonden have low motivation and as many as 27,8% of respondent have behavior of usage of PPE which is not good. The result of bivariate analysis shows that there is a significant correlation between work motivation and the behavior of PPE usage (p value 0,003) with medium relationship level 0,448. The conclusion is that there is a significant correlation between work motivation and the behavior of PPE usage on medical waste officer in Bangli General Hospital